Analysis of Public Satisfaction at the Bengkalis Regency Population and Civil Registration Office Riau Province Indonesia - Zulfikar Hasan; Risma Junita; Sri Ika Mulia; Ika Kurnia Sofiani; Mohd Helmi Ali (Universitas Teuku Umar, 2023)
The purpose of this study was to analyze the satisfaction of service quality at the Department of Population and Civil Registry of Bengkalis Regency. The research carried out is a descriptive qualitative study, in which the researchers not only distribute questionnaires but also conduct in-depth interviews with the heads of related units at the Bengkalis Regency Population and Civil Registry Office. In general, all the 14 assessment indicators got an average score of 72.4 which means good. While the service element that gets the highest score is service procedure of 3.24, and the lowest is service security. This study provides an overview that can be used by the Department of Population and Civil Registry of Bengkalis Regency to evaluate all units related to community services. Community satisfaction in this study uses the Community Satisfaction Index (CSI) and the Importance Performance Analysis (IPA) which has been published by the Ministry of Administrative Reform through the Decree of the Minister of State Apparatus Empowerment Number: KEP/25/M.PAN/2/2004. The method used in this research is Servqual, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI) with 200 respondents selected by convenience technique. In general, the value obtained by the Department of Population and Civil Registry of Bengkalis Regency using the Community Satisfaction Index is 2,896 x 25 = 72.4. This means that the performance of the service unit of the Department of Population and Civil Registry of Bengkalis Regency is in service quality